Analisis Kemampuan Kerja, Motivasi Dan Fasilitas Kerja Terhadap Kinerja Karyawan Pada CV. Suntech Grafika - Rizky Syahputra; Sri Rahayu; Hasrul Azwar Hasibuan (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This study aims to examine the effect of work ability, work motivation and work facilities on employee performance at CV. Suntech Grafika, both partially and simultaneously. Using quantitative data analysis and SPSS software, this study measures the relationship between these variables through descriptive statistics and multiple correlations. The results of the study indicate that partially, job placement and motivation do not have a positive or significant effect on employee performance. However, work facilities are proven to have a positive and significant effect on performance. Simultaneously, the combination of job placement, motivation, and work facilities also have a positive and significant effect on employee performance at CV. Suntech Grafika.